Demonstrating the need for injury prevention services in an urban community. (7th October 2012) - Shields, W; Frattaroli, S; McDonald, E; Gielen, A
Abstract : Background: Injuries from burns, scalds and carbon monoxide (CO) remain serious hazards in urban environments internationally. In preparation for a community intervention, trial baseline data was collected from a sample of homes in 12 census tracts to establish comparability between communities. Aims/Objectives/Purpose: To report on baseline knowledge and observed safety behaviours for fire, scald and CO in a large urban sample. Methods: Pairs of data collectors visited a random sample of homes in 12 census tracts. Residents completed an interview administered survey. The survey consisted of demographic data, knowledge and observed safety behaviours. Following the survey, data collectors tested the temperature of the hot water and all CO and smoke alarms. Results/Outcome: Data were collected from 603 homes between July and December 2009. A majority of respondents were African American (61%), female (70%), between the ages of 25 and 54 (66%), and had a high school education or less (51%). A majority of respondents (74%) reported a per capita income of US25 000 or less and (52%) reported renting their home. Children (<18) lived in 40% of households. A minority of households (40%) had working smoke alarms on every level, or a working CO alarm (28%). A majority of households (57%) of the households had safe (<120 F) hot water temperatures. Knowledge scores were varied across topics areas. Significance/Contribution to the Field: The study demonstrate the need for continued efforts to promote live saving injury prevention counter measures such as smoke alarms and CO alarms as well as the need for testing hot water temperatures in our urban environment.